Evaluation of behavioural, chemical, toxicological and clinical studies of a tobacco heated product glo™ and the potential for bridging from a foundational dataset to new product iterations. (2022) - Goodall, Sharon; Gale, Nathan; Thorne, David; Hadley, Simone; Prasad, Krishna; Gilmour, Ian; Miazzi, Fabio; Proctor, Christopher
Abstract: Background: Tobacco Heating Products (THPs) are tobacco products that heat rather than burn tobacco with temperatures less than 350 °C. Because of this operating principle, they produce substantially fewer and lower levels of tobacco smoke toxicants than combustible cigarette smoke produced when tobacco is burnt, which occurs at much higher temperatures of around 900 °C. This paper analyses data on a THP, glo™, and assesses whether its use would result in reduced health risks compared to the health risks of smoking cigarettes. It also looks at the possibility of bridging datasets across the different variants of the glo™ product. Methods: The approach is to consider whether datasets from behavioural, chemical, toxicological and clinical studies provide consistent findings of reductions in toxicant exposure with glo™ use by subjects who switch completely from smoking cigarettes to using glo™ and whether these reductions are similar to those who stop smoking cigarettes without switching to glo™ or any other tobacco or nicotine product. We also examine the similarities and differences of different versions of the glo™ product and benchmark it against a THP from another manufacturer. Results: The studies indicate that the use of the glo™ results in substantial and prolonged reductions in toxicant exposure for smokers who switch to glo™ completely. A long-term clinical study shows substantial reductions in toxicant exposure over a period of time, similar to reduction of some biomarkers of exposure found following smoking cessation without switching to glo™ or any other tobacco product, and biomarkers of potential harm trending in a favourable manner for both groups that switch to glo™ and that quit all tobacco and nicotine use. Data suggests that all iterations of glo™ result in substantial reductions in toxicant exposure compared to smoking cigarettes and that bridging across datasets is feasible. Conclusions: Given the accumulated scientific data summarised in this paper, and particularly the findings from a long-term clinical study, the data demonstrate that glo™ is a reduced exposure product compared to combustible cigarettes and is reasonably deemed to reduce the risk of smoking-related diseases and supports the conclusion that smokers who would have otherwise continued to smoke and instead switch entirely to THP glo™ use, will reduce their relative risk of developing smoking-related diseases as compared to continued smoking. The extent of reduction in risk compared to continuing to smoke is likely to vary by smoking-related disease and by an individuals' smoking history, other risk factors and an individual's susceptibility to disease. Use of the THP will present some level of increased health risk as compared to cessation of tobacco and nicotine products and will cause dependence. As long as the principles of heat-not-burn are maintained, THP use will result in substantially reduced exposure to smoke toxicants as compared to continued conventional cigarette smoking. It is possible to use bridging or read across to apply these conclusions to new iterations of the glo™ product, extending the utility and validity of the evidence generated through study of prior iterations. Graphical Abstract: ga1